Studi Spesies Gastropoda di Perairan Sungai Berumun - Nurlina Nurlina; Arman Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The aim of the Gastropod species study is to determine the diversity and density of Gastropods and the environmental conditions that influence the development of gastropods in berumun rivers. The research method used in this study of gastropod species is to provide descriptive information about the diversity of gastropod species in the Berumun river, Panai Hulu sub-district, Labuhan Batu district. The results of temperature measurements at the observation station in Sungai Berumun, Panai Hulu District, Labuhan Batu Regency, showed that the highest pH was at the third station, 7.40, while the lowest pH was at the first station, namely 7.1. From the results of the study, it was concluded that there are 15 species of macrozoobenthos found in the Barumun River which belong to 5 families, namely: 1. Potamididae, Cerithidae obtusa, Cerithidae alata, Cerithidae cingulata, Telescopium mauritsi, Telescopium telescopium, 2. Littorinidae, Littoraria melanostoma, Littoraria conica, Littoraria scabra, 3. Neritidae, Nerita balteata, Neritina violacea, Neritina cornucopia, 4. Muricidae, Stramonita gradata, Chicoreus capucinus, 5. Ellobiidae, Cassidula aurisfelis, Ellobium aurisjudae. Keywords: Gastropods, Diversity